Antara Resignation dan Help-Seeking: Navigasi Konflik Pekerjaan-Keluarga pada Perempuan Madura - Arifah, Nur Aina (The Sociology of Islam, 2025)
At this time, when globalization and industrialization have become commonplace, bringing excesses for changes in values in viewing gender roles and work. The shift system and the division of labor in the family often lead to mutual dependence as well as conflict. This study aims to find out in depth how Madurese women view work-family role conflicts, the dimensions of the conflicts that occur and the strategies developed by Madurese women to overcome work-family conflicts. Information was determined purposively with the following characteristics: Adult women aged between 30-50 years, working at the same time as housewives, accompanied by work-family conflicts and had conflict resolution strategies. Collecting data using in-depth interviews, observation and document studies. The results showed that from 3 informants there were 2 informants who caused time-based work interference with family and 1 informant caused behavior-based family interference with work. Conflict resolution strategies or coping mechanisms used to resolve work-family conflicts by trying to be unburdened (resignation coping) and seeking social support. Another finding, the three informants view work-family conflict as part of the nature of life and all informants develop an attitude of acceptance of the life they live even though not everything is as expected.